Spindle Cell Epulis in an 8-Month-Old Child: A Histologic Variant of Congenital Granular Cell Epulis? - Prigkos, Andreas-Christoforos (Springer US, 2012)
A case of an epulis in an 8-month-old boy is reported. The tumor was localized on the mandibular alveolar ridge and, according to the parents, was a recurrence of a congenital tumor excised when the boy was 2 months old. Microscopically, it was composed of many spindled or ovoid cells with vesicular nuclei and non-granular eosinophilic cytoplasm, and covered by acanthotic parakeratinized squamous epithelium with broad rete pegs. Immunohistochemically, the spindled and ovoid cells were intensely positive for vimentin and neuron-specific enolase, and negative for S-100 protein. The final diagnosis was spindle cell epulis. The possible correlation of this lesion with congenital granular cell epulis is discussed.